2023
DOI: 10.1038/s41467-023-36023-z
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphism in TDP-43 prion-like domain determines chaperone recognition

Abstract: The RNA binding protein TDP-43 forms cytoplasmic inclusions via its C-terminal prion-like domain in several neurodegenerative diseases. Aberrant TDP-43 aggregation arises upon phase de-mixing and transitions from liquid to solid states, following still unknown structural conversions which are primed by oxidative stress and chaperone inhibition. Despite the well-established protective roles for molecular chaperones against protein aggregation pathologies, knowledge on the determinants of chaperone recognition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 92 publications
6
19
0
Order By: Relevance
“…ALS-associated mutations may inhibit DnaJC7 interaction with other chaperones (i.e., Hsp70 and Hsp90) and thus impair substrate (tau) handoff into the chaperone-mediated protein refolding cycle. This agrees with previous observations that DnaJC7 cooperates with other chaperones to mitigate FUS and TDP-43 toxicity in yeast and in vitro 28,26 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…ALS-associated mutations may inhibit DnaJC7 interaction with other chaperones (i.e., Hsp70 and Hsp90) and thus impair substrate (tau) handoff into the chaperone-mediated protein refolding cycle. This agrees with previous observations that DnaJC7 cooperates with other chaperones to mitigate FUS and TDP-43 toxicity in yeast and in vitro 28,26 .…”
Section: Discussionsupporting
confidence: 93%
“…We have previously found that the TPR2B domain mediates DnaJC7 binding to tau 15 . Additionally, DnaJC7 was recently shown to bind the prion-like domain of the ALS-associated protein TDP-43 and mitigate its ability to phase separate in vitro 26 . To test whether these disease-associated mutations can also affect how DnaJC7 modulates tau seeding, we introduced each mutation individually into the Ruby-DnaJC7 construct.…”
Section: Disease-associated Dnajc7 Mutations Differentially Modulate ...mentioning
confidence: 99%
“…Of the tested HSP40s, DNAJA2 most effectively suppressed aggregation of co-transfected GFP-TDP43ΔNLS relative to the GST control in our experimental conditions (Figure 1D). Given that DNAJA2 was recently demonstrated to selectively bind to and reduce the phase separation of the TDP-43 LCD (49), our results support DNAJA2 as a representative suppressor of TDP-43 aggregation.…”
Section: Resultssupporting
confidence: 77%
“…Protein refolding has been considered a worldwide difficult problem because large amounts of insoluble and inactive aggregates (inclusion bodies) [1,2] were formed during the production of recombinant proteins used in the biomedical field. [3][4][5] DOI: 10.1002/mabi.…”
Section: Introductionmentioning
confidence: 99%
“…Protein refolding has been considered a worldwide difficult problem because large amounts of insoluble and inactive aggregates (inclusion bodies) [ 1,2 ] were formed during the production of recombinant proteins used in the biomedical field. [ 3–5 ] With the in‐depth study of the protein folding mechanism, it has been clear that there is a kind of sophisticated machinery, the molecular chaperones, for efficiently assisting protein with the acquirement of its native conformation and bioactivity in living systems via minimizing protein aggregation and facilitating protein refolding.…”
Section: Introductionmentioning
confidence: 99%